Listeriosis associated with pre-prepared sandwich consumption in hospital in England, 2017. (30th September 2021) - McLauchlin, J.; Aird, H.; Amar, C.; Boyd, G.; Brindle, A.; Dallman, T.; Jalava, K.; Painset, A.; Simbo, A.; Swindlehurst, M.
Abstract: A case of listeriosis occurred in a hospitalised patient in England in July 2017. Analysis by whole genome sequencing of the Listeria monocytogenes from the patient's blood culture was identified as clonal complex (CC) 121. This culture was indistinguishable to isolates from sandwiches, salads and the maufacturing environment of Company X which supplied these products widely to the National Health Service. Whilst an inpatient, the case was served sandwiches produced by this company on 12 occasions. No other cases infected by this type were detected in the UK between 2016 and 2020. Between 2016 and 2020, more than 3000 samples of food, food ingredients and environmental swabs from this company were tested. Listeria monocytogenes contamination rates declined after July 2017 from 31% to 0.3% for salads and 3% to 0% for sandwiches. A monophyletic group of 127 L. monocytogenes CC121 isolates was recovered during 2016–2019 and was used to estimate the time of the most recent common ancestor as 2014 (95% CI of between 2012 and 2016). These results represent persistent contamination of equipment, food contact surfaces and foods at a food manufacturer by a single L. monocytogenes strain. Colonisation and persistent contamination of food and production environments are risks for public health.